2013
DOI: 10.1111/j.1365-2265.2012.04486.x
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt decrease in serum testosterone levels after an oral glucose load in men: implications for screening for hypogonadism

Abstract: Glucose ingestion induces a significant reduction in total and free T levels in men, which is similar across the spectrum of glucose tolerance. This decrease in T appears to be because of a direct testicular defect, but the absence of compensatory changes in LH suggests an additional central component. Men found to have low nonfasting T levels should be re-evaluated in the fasting state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 37 publications
4
81
0
5
Order By: Relevance
“…It has been demonstrated that glucose administration impacts TT levels in men without preexisting androgen deficiency with implications for the biochemical categorization of androgen status. A standard 75-g OGTT resulted in a 25% reduction in serum TT levels across a range of BMIs and glucose tolerance with 15% of men recording a TT level of <9.7 nmol l −1 on at least one occasion during the 120-min sampling period,64 confirming earlier observations 65. SHBG and LH levels (measured at 5 time points) were unchanged, however, a deconvolution analysis study of 50 men with age range of 18–80 years and BMI range of 20–40 kg m −2 with normal baseline glucose tolerance66 demonstrated a glucose-induced fall in pulsatile LH secretion, which was exacerbated by higher fasting insulin concentrations.…”
Section: The Impact Of Acute Changes In Glucose and Insulin On Testosmentioning
confidence: 99%
“…It has been demonstrated that glucose administration impacts TT levels in men without preexisting androgen deficiency with implications for the biochemical categorization of androgen status. A standard 75-g OGTT resulted in a 25% reduction in serum TT levels across a range of BMIs and glucose tolerance with 15% of men recording a TT level of <9.7 nmol l −1 on at least one occasion during the 120-min sampling period,64 confirming earlier observations 65. SHBG and LH levels (measured at 5 time points) were unchanged, however, a deconvolution analysis study of 50 men with age range of 18–80 years and BMI range of 20–40 kg m −2 with normal baseline glucose tolerance66 demonstrated a glucose-induced fall in pulsatile LH secretion, which was exacerbated by higher fasting insulin concentrations.…”
Section: The Impact Of Acute Changes In Glucose and Insulin On Testosmentioning
confidence: 99%
“…There is also evidence that testosterone regulates insulin sensitivity directly and acutely (Yialamas et al 2007). Interestingly, a reciprocal feedback also appears to exist, given that not only chronic (Cameron et al 1990, Allan 2013 but also, as shown more recently (Iranmanesh et al 2012, Caronia et al 2013, acute hyperglycaemia can lower testosterone levels.…”
Section: End Organ Deficits Of Androgen Deficiencymentioning
confidence: 99%
“…Although the exact mechanism by which this reduction occurs remains unclear, none of the previous studies observed any significant change in SHBG concentrations either following a glucose load [10, 11] or administration of meals [5, 8, 9], suggesting that the fall in serum testosterone is real and not simply a reflection of reduction in serum SHBG levels. What remains unclear is whether this decline in testosterone is due to a central process or secondary to reduced testicular secretion as some previous studies reported an increase in LH levels while others showed no change [6, 8, 10]. In the current study, we did not observe any significant change in serum LH levels following either a glucose load or mixed meal despite measuring serum LH levels at multiple time points in both cohorts.…”
Section: Discussionmentioning
confidence: 99%